"She Was a Little Social Butterfly": A Qualitative Analysis of Parent Perception of Social Functioning in Adolescent and Young Adult Brain Tumor Survivors. (July 2017) - Wilford, Justin; Buchbinder, David; Fortier, Michelle A.; Osann, Kathryn; Shen, Violet; Torno, Lilibeth; Sender, Leonard S.; Parsons, Susan K.; Wenzel, Lari
Psychosocial sequelae of diagnosis and treatment for childhood brain tumor survivors are significant, yet little is known about their impact on adolescent and young adult (AYA) brain tumor survivors. Interviews were conducted with parents of AYA brain tumor survivors with a focus on social functioning. Semistructured interviews were conducted with English- and Spanish-speaking parents of AYA brain tumor survivors ≥10 years of age who were >2 years postdiagnosis, and analyzed using emergent themes theoretically integrated with a social neuroscience model of social competence. Twenty parents representing 19 survivors with a survivor mean age 15.7 ± 3.3 years and 10.1 ± 4.8 years postdiagnosis were interviewed. Several themes relevant to the social neuroscience social competence model emerged. First, parents' perceptions of their children's impaired social functioning corroborated the model, particularly with regard to poor social adjustment, social withdrawal, impaired social information processing, and developmentally inappropriate peer communication. Second, ongoing physical and emotional sequelae of central nervous system insults were seen by parents as adversely affecting social functioning among survivors. Third, a disrupted family environment and ongoing parent psychosocial distress were experienced as salient features of daily life. We document that the aforementioned framework is useful for understanding the social impact of diagnosis and treatment on AYA brain tumor survivorship. Moreover, the framework highlights areas of intervention that may enhance social functioning for AYA brain tumor survivors.